3D Play Fairway Analysis for Delineating Exploration Targets in the Tulehu Geothermal Field, Indonesia - Agusta Asri, Hamdani (International Journal Labs, 2025)
The Tulehu geothermal field in Maluku, Indonesia, is a strategic asset whose development faces challenges related to exploration risks. Previous drilling of four exploration wells has not consistently yielded adequate permeability and/or temperature results for commercial-scale development. This failure highlights the need for a more systematic approach to reduce drilling risk. This study aims to determine the optimal subsurface target using the Play Fairway Analysis (PFA) method within a 3D framework. This method quantitatively evaluates and integrates key geothermal system parameters, namely heat, permeability, cap rock, and drilling economic viability, based on existing geological, geophysical, and well data. Each parameter is transformed into a spatial index model and combined through a weighting scheme to produce a Favourability Index Model. The modeling results indicate that the area with the highest favorability (index > 0.91) is located south to southeast of the Banda Fault, at elevations between -784 m and -2,068 m. These prospective locations align with evidence from the productive feed zone in well TLU-B-02, indicating that previous interpretations of fault geometry need to be revised. These modeling results provide a strong scientific basis for identifying and prioritizing subsurface drilling targets, thereby reducing exploration risk in subsequent development phases.